Poverty, food insecurity, and health of Palestinian refugees in Lebanon and recently displaced from Syria to Lebanon: findings from the 2015 socioeconomic household survey. (21st February 2018) - Ghattas, Hala; Chaaban, Jad; Salti, Nisreen; Irani, Alexandra; Ismail, Tala; Batlouni, Lara
Abstract: Background: The United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) provides health, education, and housing services to Palestinian refugees in Lebanon (PRL), and food assistance and welfare support to the most vulnerable refugees. Palestinian refugees recently displaced from Syria (PRS) to Lebanon have placed additional pressures on health and education services, and employment rights of Palestinians remain limited. The objective of this study was to provide an updated profile of the socioeconomic and health status of PRL and PRS after their influx into Lebanon. Methods: This nationally representative, multistage, cluster randomised survey of PRL and PRS households was done in April, 2015. Modules on socioeconomic, demographic, health, and food security variables were included. The poverty lines were US$6·84 per person per day for PRL households and $2·47 per person per day for PRS households. Food insecurity was assessed using the Arab Family Food Security Scale. Health conditions were reported for all household members by a household proxy. We used STATA version 13.0 to construct multivariate models to investigate independent predictors of poverty, food insecurity, and chronic disease. The study was approved by the Institutional Review Board of the American University of Beirut. Findings: 2974 (88%) of the 3382 eligible PRL and 1050 (89%) of 1171 eligible PRS households gave informed consent and completed the questionnaire. 65% of PRL and 89% of PRS lived under the poverty line, whereas 3% of PRL and 9% of PRS were extremely poor. 62% of PRL and 95% of PRS were food insecure. Household size, unemployment, and low educational attainment of the head of household were associated with both poverty and food insecurity in PRL and PRS households. The prevalence of chronic illness was high in PRL and PRS households, with chronic disease in PRL households reported for 40% of people aged 19–59 years and for 88% of elderly adults (aged >60 years), and chronic disease in PRS households reported for 41% of people aged 19–59 years and for 86% of elderly adults. Chronic illness was independently associated with education and employment, household size, food insecurity, and area of residence. Interpretation: Palestinian refugees in Lebanon and those recently displaced from Syria to Lebanon are susceptible to poverty, food insecurity, and chronic illnesses, which vary with similar sociodemographic markers (mainly employment and education). Advocacy is needed to increase employment rights and ensure continued access to education and health services for Palestinians living in Lebanon, particularly with pressures on services resulting from the Syrian crisis. Funding: UNWRA.